Responses of Platycerium Coronarium (Koenig.) Dev and Platycerium Bifurcatum (Cav.) c. chr. to Light and Water Stress in Nursery Enviroment - Mohd Sanusi, Ruzana Adibah (2011)
Environmental changes have enormous effects especially on plants physiology and growth. These changes will have significant impact on the growth and survival of plants in the changing of future climates. Canopy plants especially epiphytes which live in the forest canopy play an important role to their surroundings. Thus, this study was conducted to evaluate the growth and physiological response of Platycerium coronarium and Platycerium bifurcatum towards light and water stress. In light stress study, both species were grown under four treatments namely 20 μmol m-2s-1 (T1), 70 μmol m-2s-1 (T2), 200 μmol m-2s-1 (T3) and 1500 μmol m-2s-1 (T4). In water stress study, they were divided into five treatments which were watered once everyday (T1), watered to field capacity (T2), watered once in two weeks (T3), watered once in three weeks (T4) and not watered (T5). Growth responses were evaluated through the leaf length measurement, leaf area, sporotrophophyll weight, cover leaves weight, total dry weight and total leaf water content. Physiological responses were quantified by leaf gas exchange, chlorophyll fluorescence and whole plant transpiration rate. All measurements were carried out weekly for twelve weeks. Two experiments were conducted to determine whether both species were CAM plants by determining their leaf acidity and carbon 13 isotope (δ13 C) ratio. In light stress treatment, leaf length and leaf area of P. coronarium, was statistically different between treatments (p≤0.05). However, T1 had the lowest value in all growth parameters. Lowest light intensity reduces growth for this species. For P. bifurcatum, total leaf length was significantly different between treatments (p≤0.05). Higher light intensity treatment causes reduction in leaf length for this species. All leaf gas exchange parameters for P. coronarium were statistically different except for Ci (p≤0.05). However, highest light intensity (T4) reduces the Anet, D and WUE value. All treatments also had the value of Fv/Fm of healthy plant in the range from 0.82 to 0.84. P. coronarium were moderately affected in its physiological activity. For P. bifurcatum, significant differences were found for Anet, EL and WUE (p≤0.05). Highest light intensity (T4) showed lowest value in Anet. Fv/Fm in T3 and T4 were below 0.8 indicating that there was a sign of stress. P. bifurcatum was affected under high light intensity. Both species had no higher accumulation of acids at dusk compared to early morning and δ13 C showed both species are C3 plant thus suggesting that both species did not initiate CAM. In water stress treatments, total leaf length and leaf water content of P. coronarium, were significantly different for all treatments (p≤0.05). While for P. bifurcatum,significant differences were found in total leaf length, leaf area and leaf water content (p≤0.05). Higher water stress treatment (T5) reduced growth performance of both species. Anet, gs, EL, D and WUE were significantly different in all treatments of P. coronarium (p≤0.05). For P. bifurcatum, significant differences were found in Anet, gs, EL and D (p≤0.05). T5 reduced Anet,. gs and EL, however its Fv/Fm value was above 0.8 in both species. Both species was moderately affected by water stress. Higher acid accumulation was observed in early morning compared to dusk samples and all treatments were found to have C3 photosynthesis for both species. Therefore this indicates that water stress did not alter physiological pathway for both species.